Integrating superconducting van der Waals materials on paper substrates. Issue 10 (13th April 2021) - Azpeitia, Jon; Frisenda, Riccardo; Lee, Martin; Bouwmeester, Damian; Zhang, Wenliang; Mompean, Federico; van der Zant, Herre S. J.; García-Hernández, Mar; Castellanos-Gomez, Andres
Abstract : Paper has the potential to dramatically reduce the cost of electronic components but the integration of electronic materials is challenging. Here the integration of NbSe2, a van der Waals superconductor, on paper is demonstrated. Abstract : Paper has the potential to dramatically reduce the cost of electronic components. In fact, paper is 10 000 times cheaper than crystalline silicon, motivating the research to integrate electronic materials on paper substrates. Among the different electronic materials, van der Waals materials are attracting the interest of the scientific community working on paper-based electronics because of the combination of high electrical performance and mechanical flexibility. Up to now, different methods have been developed to pattern conducting, semiconducting and insulating van der Waals materials on paper but the integration of superconductors remains elusive. Here, the deposition of NbSe2, an illustrative van der Waals superconductor, on standard copy paper is demonstrated. The deposited NbSe2 films on paper display superconducting properties ( e.g. observation of Meissner effect and resistance drop to zero-resistance state when cooled down below its critical temperature) similar to those of bulk NbSe2 .